EFEKTIVITAS PEMBERIAN TUMIS DAUN PEPAYA TERHADAP KELANCARAN ASI PADA IBU NIFAS DI POSKESDES TAMERAN KABUPATEN BENGKALIS - Rosidah, Rosidah; Aifa, Wira Ekdeni; Mardiya, Rizka; Susanti, Komaria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The production and smooth flow of breast milk (ASI) are critical factors in the success of exclusive breastfeeding. One natural approach to enhance milk flow is through the use of local food sources that function as galactagogues, such as papaya leaves (Carica papaya L.). Objective: This study aims to determine the effectiveness of sautéed papaya leaves in improving breast milk flow among postpartum mothers at the Tameran Village Health Post (Poskesdes), Bengkalis Regency. Method: This research employed a pre-experimental design with a one- group pre-test and post-test approach. A total of 14 postpartum mothers participated as respondents. Breast milk flow was measured before and after the intervention using an observation scale and analyzed with the Wilcoxon Signed Ranks Test. Results: Prior to the intervention, only 21.4% of the mothers experienced smooth breast milk flow, with a mean score of 4.36 (SD = 1.082). After consuming sautéed papaya leaves, the proportion of mothers with smooth milk flow increased to 64.3%, with a mean score of 5.64 (SD = 0.497). The Wilcoxon test yielded a p value of 0.002 (p < 0.05), indicating a statistically significant difference before and after the intervention. Conclusion: Sautéed papaya leaves have been proven effective in improving breast milk flow in postpartum mothers. The use of local food sources may serve as a non-pharmacological intervention at the primary healthcare level. Recommendation: It is recommended that health workers at Poskesdes and community health centers utilize papaya leaves as an educational alternative to support successful breastfeeding, and that further studies be conducted using experimental designs with comprehensive hormonal measurements.Keywords: Papaya Leaves, Breast Milk Flow, Postpartum Mothers